- 1-214-256-5804
- info@tutorpace.com

5 – 3 (5x + 2) = 4 (7- 3x) + 1

5 – 3 (5x + 2) = 4 (7- 3x) + 1

5 – 15x – 6 = 28 – 12x +1 [Distributing the terms within parenthesis]

-15x -1 = -12x + 29 [On Simplifying the like terms we get]

- 15x + 12x = 29 + 1 [Isolating the variable on one side and the constant on other side]

(- 3)x = 30 [Divide both sides by -3 and we will get]

x = -10

The sum of two numbers is 90 and the greater number exceeds thrice the smaller by 14.Find the numbers.

Let the smaller number be x.

As the sum of the two numbers is 90, then the greater number will be 90 – x.

Thrice the smaller number will be 3x

So the equation becomes:

90 – x = 3x + 14

-x -3x = 14 – 90 [Isolating the variable on one side and the constant on other side]

(-4)x = - 76 [Divide both sides by -4 and we will get]

x = 19

Then the greater number will be 90 – x = 90 – 19 = 71

Hence the two numbers are 19 and 71.